2017
DOI: 10.1080/13548506.2016.1271955
|View full text |Cite
|
Sign up to set email alerts
|

School corporal punishment in global perspective: prevalence, outcomes, and efforts at intervention

Abstract: School corporal punishment continues to be a legal means of disciplining children in a third of the world's countries. Although much is known about parents' use of corporal punishment, little is known about school corporal punishment. This article summarizes what is known about the legality and prevalence of school corporal punishment, about the outcomes linked to it, and about interventions to reduce and eliminate school corporal punishment around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 33 publications
(48 reference statements)
3
166
1
7
Order By: Relevance
“…However, even in countries with a legal prohibition, corporal punishment in schools continues to be widespread. Gershoff reported the prevalence of school corporal punishment in 29 countries with a legal ban and the prevalence estimates ranged from 13% to 97% . Thus, while legislative reform is necessary, additional actions are required including advocacy and public education campaigns and training for teachers in positive discipline practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in countries with a legal prohibition, corporal punishment in schools continues to be widespread. Gershoff reported the prevalence of school corporal punishment in 29 countries with a legal ban and the prevalence estimates ranged from 13% to 97% . Thus, while legislative reform is necessary, additional actions are required including advocacy and public education campaigns and training for teachers in positive discipline practices.…”
Section: Discussionmentioning
confidence: 99%
“…Gershoff reported the prevalence of school corporal punishment in 29 countries with a legal ban and the prevalence estimates ranged from 13% to 97%. 56 Thus, while legislative reform is necessary, additional actions are required including advocacy and public education campaigns and training for teachers in positive discipline practices. Although the Irie Classroom Toolbox was developed for the Jamaican preschool context, the content and process of training is likely to have wide applicability to other LMIC with an established preschool network.…”
Section: Discussionmentioning
confidence: 99%
“…School children around the world are subject to different forms of violence, at the hands of teachers and authority figures. School teachers often use a variety of methods to inflict punishment for a very diverse, and often innocuous range of student behaviours (Gershoff, 2017). These methods of punishment cause emotional humiliation, physical injury and in rare cases, even death.…”
Section: Violence In Schools (Learning Group 2)mentioning
confidence: 99%
“…The normalisation of violence against boys renders invisible the threats they face. For instance, two countries legally permit corporal punishment in schools for boys alone (Gershoff, 2017). Boys entering adolescence are vulnerable to peer group pressure to join gangs and engage in criminal activity.…”
Section: Unpacking the Age And Gender Dimensions Of Violence (Learninmentioning
confidence: 99%
“…The table also shows the destruction that punishment causes for students. Studies conducted have shown that punishment -and especially physical punishment -can increase aggressiveness, and it can also influence mental health (Gershoff, 2002;Gershoff, 2017; Ghosh& Banerjee, 2016).…”
mentioning
confidence: 99%